2017
DOI: 10.1016/j.ijheh.2017.04.001
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of parallel dust and fibre measurements of airborne chrysotile asbestos in a large mine and processing factories in the Russian Federation

Abstract: Our study shows that dust to fibre conversion is possible by unit but extrapolations are needed. The patterns for exposure by dust and fibre will be similar but estimated fibre levels will show less contrast due to the conversion factor being smaller at higher dust concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…The ORs of LLF, PD, and LM in two categories, neighborhood factory exposure >20 years and slate roof exposure in a slate roof-dense area, were increased in all models (Table 5). of asbestos-containing materials was associated with higher prevalence rates of LLF and PD, compared to the occupational use of asbestos products [17]. The previous finding that low levels of occupational, household, and neighborhood exposure may induce pleural plaques [18] is consistent with our results.…”
Section: Logistic Regression Analysissupporting
confidence: 92%
“…The ORs of LLF, PD, and LM in two categories, neighborhood factory exposure >20 years and slate roof exposure in a slate roof-dense area, were increased in all models (Table 5). of asbestos-containing materials was associated with higher prevalence rates of LLF and PD, compared to the occupational use of asbestos products [17]. The previous finding that low levels of occupational, household, and neighborhood exposure may induce pleural plaques [18] is consistent with our results.…”
Section: Logistic Regression Analysissupporting
confidence: 92%
“…Fiber concentration is generally the preferred metric for assessing health outcomes from asbestos exposure because dust encompasses other airborne materials in addition to asbestos fibers ( Harries, 1971 ; Dement et al , 2008 ). A limited number of parallel dust and fiber measurements available for The Asbest Study have been used to derive dust-to-fiber conversion factors that may be applied to estimate fiber levels for the planned risk analyses ( Feletto et al , 2017 ). In Brazil, Bagatin et al (2005) reported the annual fiber concentrations throughout a chrysotile asbestos mine and mills between 1977 and 1993.…”
Section: Discussionmentioning
confidence: 99%
“…Since the late 1800s, there have been 7 asbestos-enrichment processing mills (called factories) operated by JSC Uralasbest, each of which conducted the same chrysotile-enrichment process, but with varying technology and machinery used. Over time, the degree of mechanization has advanced and technologies have improved, permitting the enrichment of ore with lower chrysotile content and resulting in reduced exposures to airborne dust and fibres in the work environment [ 20 , 21 ]. All factories used the dry milling technique, which consists of repeated cycles of crushing the raw ore, drying, and then screening through vibrating screeners so that chrysotile fibres rise to the surface and are removed by vacuum suction.…”
Section: Cohort Descriptionmentioning
confidence: 99%
“…For each job, an annual average dust concentration was estimated, which was derived from measurements taken at the measurement points applicable to that job (note that jobs with mobility of workers may have involved several measurement points). In the mine, the annual average was weighted by season, by calculating first averages for the winter and the summer period and weighing them 2:1 to reflect the relative length of winter versus summer in this area [ 21 ]. Estimated annual average concentrations were linked to each cohort member based on the job performed in each calendar year and adjusted for the proportion of the year that the worker had actually worked.…”
Section: Cohort Descriptionmentioning
confidence: 99%
See 1 more Smart Citation